Administration of Tauroursodeoxycholic Acid Attenuates Early Brain Injury via Akt Pathway Activation - Sun, Dongdong; Gu, Gang; Wang, Jianhao; Chai, Yan; Fan, Yueshan; Yang, Mengchen; Xu, Xin; Gao, Weiwei; Li, Fei; Yin, Dongpei; Zhou, Shuai; Chen, Xin; et al. (Frontiers in Cellular Neuroscience, 2017)
Traumatic brain injury (TBI) is one of the leading causes of trauma-induced mortality and disability, and emerging studies have shown that endoplasmic reticulum (ER) stress plays an important role in the pathophysiology of TBI. Tauroursodeoxycholic acid (TUDCA), a hydrophilic bile acid, has been reported to act as an ER stress inhibitor and chemical chaperone and to have the potential to attenuate apoptosis and inflammation. To study the effects of TUDCA on brain injury, we subjected mice to TBI with a controlled cortical impact (CCI) device. Using western blotting, we first examined TBI-induced changes in the expression levels of GRP78, an ER stress marker, p-PERK, PERK, p-eIF2α, eIF2α, ATF4, p-Akt, Akt, Pten, Bax, Bcl-2, Caspase-12 and CHOP, as well as changes in the mRNA levels of Akt, GRP78, Caspase-12 and CHOP using RT-PCR. Neuronal cell death was assessed by a terminal deoxynucleotidyl transferase (TdT)-mediated dUTP nick end-labelling (TUNEL) assay, and CHOP expression in neuronal cells was detected by double-immunofluorescence staining. Neurological and motor deficits were assessed by modified neurological severity scores (mNSS) and beam balance and beam walking tests, and brain water content was also assessed. Our results indicated that ER stress peaked at 72 h after TBI and that TUDCA abolished ER stress and inhibited p-PERK, p-eIF2α, ATF4, Pten, Caspase-12 and CHOP expression levels. Moreover, our results show that TUDCA also improved neurological function and alleviated brain oedema. Additionally, TUDCA increased p-Akt expression and the Bcl-2/Bax ratio. However, the administration of the Akt inhibitor MK2206 or siRNA targeting of Akt abolished the beneficial effects of TUDCA. Taken together, our results indicate that TUDCA may attenuate early brain injury via Akt pathway activation.